Transience and Place: Exploring Tourists’ Experiences of Place - Jacobsen, Jens Kristian Steen (Nordlit, 1998)
This paper explores tourists' transient place experiences. The focus is on what is commonly called sightseeing, confined mainly to experiences of locations not previously visited. This type of travel experience, seeing actual places or objects for one's self and taking photographs, is regarded here as an important ritual in modernity. With reference to the concept of adventurer, the paper attempts to describe various aspects of novel travel experiences. For instance, ephemeral tourist sensations of place are compared to «love at first sight», a blissful experience of meeting with a place to which one feels strongly attracted. While transient encounters may also provide access to dreamlike place experiences, adventurous tourists are always in danger of being caught up in other roles, or of becoming embroiled in a new everyday life with accompanying routines. By way of conclusion, it is proposed that the restrictions on time inherent in today's holiday tours usually result in transient place experiences as the only alternative for those desiring to gain first-time impressions of several places or larger geographic areas.